288 Injury burden in American football. (3rd March 2020) - Johnson, Samuel; Aukerman, Douglas; Brown, Cathleen; Norcross, Marc
Abstract : Background: Both injury incidence and severity should be used to establish the extent of sports-related injuries. Previous reports for American football have presented these factors separately. Injury burden, defined as the product of incidence multiplied by severity, may provide better information for where to focus prevention efforts. Objective: Describe the injury burden for common American football injuries. Design: Prospective cohort epidemiological study. Setting: NCAA Division I University. Patients (or Participants): Athletes on the football team roster over three competitive years: 2016–17 (n=112), 2017–18 (n=114), and 2018–19 (n=109). Interventions (or assessment of risk factors): Injury diagnosis and days-lost from participation for athletes on the team as recorded by athletic trainers providing care to the team. Main outcome measurements: Injury burden as the product of injury incidence (number of injuries per 100 athlete-seasons) multiplied by severity (average days-lost from participation per injury) of eight common injuries sustained in American football. Results: Injury burden reported from highest to lowest: shoulder subluxations/dislocations (225.4 days-lost/athlete-season), anterior cruciate ligament (ACL) injuries (204.8 days-lost/athlete-season), thigh/hip muscle injuries (199.1 days-lost/athlete-season), concussions (124.5 days-lost/athlete-season), ankle sprains (103.6 days-lost/athlete-season), knee injuries other than ACL injuries (69.6 days-lost/athlete-season), patellofemoral and patellar tendon injuries (35.8 days-lost/athlete-season), and acromioclavicular joint injuries (17.6 days-lost/athlete-season). Conclusions: While not all injuries can be prevented, utilizing injury burden can help the sports medicine professional identify where prevention efforts would have maximal impact to a team. These results suggest injury prevention efforts should be directed towards shoulder subluxations/dislocations, ACL, and thigh/hip injuries. It is interesting to note that the injury burden of shoulder subluxations/dislocations and ACL injuries was primarily driven by the injury severity; while the injury burden of thigh/hip muscle injuries was driven mainly by the injury frequency.